Experiência com o currículo oficial do estado de São Paulo: contribuições para o aluno decorrentes de uma ação pedagógica pautada na ginástica de condicionamento físico - Maffei, Willer Soares [UNESP] (My University, 2014)
Presents the contributions of pedagogical actions of a teacher- researcher, based on Body Culture Movement. Such actions were developed in physical education classes for one month in the second year of secondary education of state public school, located in the interior of São Paulo. Aims to understand what are the contributions to the student arising from actions based on Gymnastics in teacher reflection, developed by a teacherresearcher. The research approach and procedures adopted for the construction of data is qualitative in nature, exploring the descriptions field diary about the classes held. The results show that the contributions of such pedagogical actions can not be verified in the short time since they refer to changes in attitude and this requires time and the opportunity to participate in experiments planned in terms of goals and purposes that not are always proposed by the interlocutors of pedagogical action, but determined by external agents, such as educational policy and those responsible for curriculum development. The value of experience lies in how the actor engages with the pedagogical situation and the senses extracted from these actions, which presupposes individually with each student receives certain experience and the meanings extracted from each experience.

Aborda as contribuições das ações pedagógicas de um professor-pesquisador, fundamentadas na Cultura Movimento. Tais ações foram desenvolvidas nas aulas de Educação Física, durante um mês, no segundo ano do Ensino Médio diurno de uma instituição pública estadual, localizada em um município do interior paulista. Buscou entender quais são as contribuições para o aluno decorrentes de ações educativas pautadas na Ginástica e na reflexão docente, desenvolvidas por um professorpesquisador. A abordagem de investigação e os procedimentos de construção de dados adotados são de natureza qualitativa, explorando descrições do diário de campo sobre as aulas realizadas. Os resultados obtidos evidenciam que as contribuições de tais ações pedagógicas não podem ser verificadas no curto espaço de tempo, uma vez que, se referem a mudanças de atitude e isso requer tempo e a possibilidade de participar de experiências planejadas em função de objetivos e finalidades que nem sempre são propostos pelos interlocutores da ação pedagógica, mas sim determinados por agentes externos, como a política educacional e os responsáveis pela elaboração do currículo. O valor da experiência reside na forma como os interlocutores se envolvem com a situação pedagógica e os sentidos advindos dessas ações, o que, pressupõe a singularidade com que cada aluno recebe determinada experiência e os significados advindos dela.
Experience with the official curriculum of the São Paulo state: contributions to the student of an action with educational content gym
Keywords: Physical Education; Teaching practice; Teacher-researcher; Educação Física; Prática pedagógica; Professor-pesquisador